PENDIDIKAN KARAKTER ISLAMI MENURUT AL-QUR’AN: Tela'ah Tartīb An-Nuzulī terhadap Nilai-Nilai Karakter - Adzka Dhiyaurrahman - (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2025)
This study explores islamic character education based on the Tartīb an-Nuzulī approach, grounded in the Manhaj Sistematika Wahyu theory developed by Abdullah Said. This theory emphasizes gradual education aligned with the chronological order of Quranic revelations to systematically shape islamic character. The study addresses the problem of weak internalization of islamic character values in society, which contributes to declining morality. The research aims to identify relevant values of islamic character education through an analysis of the first five revealed surahs of the Qur'an. Employing a qualitative library research method with descriptive analysis, the study examines Quranic verses and the Tartīb an-Nuzulī interpretation approach. The findings reveal that islamic character education begins with strengthening faith and scientific values (Surah Al-‘Alaq), followed by honesty and patience (Surah Al-Qalam), spiritual discipline (Surah Al-Muzzammil), social responsibility (Surah Al-Muddassir), and compassion and trust in Allah (Surah Al-Fatihah). This gradual approach provides practical guidance for sustainably building islamic character while considering the historical context and relevance of Quranic verses. The study offers conceptual and practical contributions to islamic character education, addressing contemporary moral challenges.